2014
DOI: 10.1016/j.celrep.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

HITS-CLIP and Integrative Modeling Define the Rbfox Splicing-Regulatory Network Linked to Brain Development and Autism

Abstract: Summary The RNA-binding proteins Rbfox1/2/3 regulate alternative splicing in the nervous system, and disruption of Rbfox1 has been implicated in autism. However, comprehensive identification of functional Rbfox targets has been challenging. Here we performed HITS-CLIP for all three Rbfox family members to globally map, at a single-nucleotide resolution, their in vivo RNA interaction sites in the mouse brain. We found that the two guanines in the Rbfox-binding motif UGCAUG are critical for protein-RNA interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
444
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(477 citation statements)
references
References 53 publications
33
444
0
Order By: Relevance
“…The similar phenotype observed for Rbfox1 and Rbfox2 KD suggests that both RBPs regulate overlapping sets of transcripts in beta cells. This is in agreement with previous studies showing that Rbfox proteins bind to the same UGCAUG motif due to the presence of a common RNA binding domain (28,32,62). Functional analysis of the role of Rbfox proteins in beta cells (present data) indicates that Rbfox depletion increases the insulin secretory capacity by affecting actin depolymerization kinetics following glucose stimulation.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 82%
See 3 more Smart Citations
“…The similar phenotype observed for Rbfox1 and Rbfox2 KD suggests that both RBPs regulate overlapping sets of transcripts in beta cells. This is in agreement with previous studies showing that Rbfox proteins bind to the same UGCAUG motif due to the presence of a common RNA binding domain (28,32,62). Functional analysis of the role of Rbfox proteins in beta cells (present data) indicates that Rbfox depletion increases the insulin secretory capacity by affecting actin depolymerization kinetics following glucose stimulation.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 82%
“…Gelsolin enhances insulin secretion by mediating glucose-dependent actin cytoskeleton remodeling and by interacting with t-SNARE proteins, thus favoring insulin granule exocytosis (29,30). In line with the present findings, Rbfox1 targets in brain and muscle are enriched in genes involved in cytoskeleton organization and actin filament-based processes (28,57). We cannot exclude, however, that other Rbfox targets (such as calcium channels) also contribute to the observed phenotype.…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellssupporting
confidence: 78%
See 2 more Smart Citations
“…S12). Rbfox and Nova are known to regulate AS of neuronal transcripts by activating or repressing exon inclusion depending on their binding position relative to the alternative exon (17,20,21). We found that both known and new cassette exons with neuron-specific inclusion 3B and SI Appendix, Fig.…”
Section: Extending the Mouse And Human Cortex Transcriptomes By Deepmentioning
confidence: 72%